KONTRIBUSI PENDIDIKAN TINGGI KEAGAMAAN BAGI KARYA PASTORAL KEUSKUPAN PALANGKARAYA - Timotius Tote Jelahu (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2021)
STIPAS Tahasak Danum Pambelum (TDP) is a Religious Higher Education under the auspices of the Tahasak Danum Pambelum Foundation of the Diocese of Palangkaraya. The background for the establishment of this Higher Education is the shortage of Pastoral Catechetics for the Diocese of Palangkaraya, especially in the field of education. It is interesting to study whether the presence of Religious Colleges contributes to pastoral work in the Diocese of Palangkaraya. This research is a document study to describe the contribution of Religious Higher Education for pastoral work in the Diocese of Palangkaraya and also in carrying out the mandate of the Act to educate the nation's life. The results of the study show that Religious Colleges have made a positive contribution to pastoral work at the Local Church of the Diocese of Palangkaraya and together with the government have contributed to carrying out the task of educating the nation's life.